Mathematical model of matrix production - Hardai, Ibolya; Illés, Béla; Bányai Tóth, Ágota (Advanced Logistic Systems - Theory and Practice, 2025)
The task of production logistics is to move workpieces within the plant between workstations, and to supply the workstations with the raw materials, components, etc. required for the given production task. This is no different in an AGV-served matrix production that complies with Industry 4.0 principles. In the case of larger workpieces, they are transported by a dedicated AGV throughout the production process. In the production space, several AGVs perform their tasks simultaneously, thus several material handling tasks occur simultaneously. This paper presents a mathematical model in detail, which allows for optimization according to various aspects. With the help of the model, we specify the objective functions and the restrictions on them.